2008
DOI: 10.1016/j.jcat.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Combined removal of diesel soot particulates and NO over CeO2–ZrO2 mixed oxides

Abstract: CeO 2 and Ce-Zr mixed oxides with different Ce:Zr ratio have been prepared, characterised by Raman spectroscopy, XRD, TEM, N 2 adsorption at -196ºC and H 2 -TPR, and tested for soot oxidation under NO x /O 2 . Among the different mixed oxides, Ce 0.76 Zr 0.24 O 2 provided the best results. Ce 0.76 Zr 0.24 O 2 presents a higher activity than pure CeO 2 for soot oxidation by NO x /O 2 when both catalysts are calcined at 500ºC (soot oxidation rates at 500ºC are 14.9 and 11.4 g soot /s, respectively), and the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(56 citation statements)
references
References 43 publications
0
55
0
1
Order By: Relevance
“…NO oxidation plays an increasingly significant role in NO x removal technologies (Bray and Schneider, 2015;Xie et al, 2017), including NO x storage and reduction (Lin et al, 2013;Zhang et al, 2016), selective catalytic reduction (Zahaf et al, 2015;Guo et al, 2017), dry sorbent injection (Rezaei et al, 2015) and absorption in wet flue gas desulfurization (Liu et al, 2014;Guo et al, 2015b). Cerium oxide has been widely utilized in catalysts pleased in these mobile source and stationary source applications, due to its outstanding oxygen storage capacity (OSC) (Atribak et al, 2008;Zhang et al, 2011;Hong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…NO oxidation plays an increasingly significant role in NO x removal technologies (Bray and Schneider, 2015;Xie et al, 2017), including NO x storage and reduction (Lin et al, 2013;Zhang et al, 2016), selective catalytic reduction (Zahaf et al, 2015;Guo et al, 2017), dry sorbent injection (Rezaei et al, 2015) and absorption in wet flue gas desulfurization (Liu et al, 2014;Guo et al, 2015b). Cerium oxide has been widely utilized in catalysts pleased in these mobile source and stationary source applications, due to its outstanding oxygen storage capacity (OSC) (Atribak et al, 2008;Zhang et al, 2011;Hong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The NOx formation by the internal combustion due the high ignition temperature is well understood but the formation soot is more complicated and difficult to examine [4,5]. It is a big challenge to control these two pollutants with the fulfillment of exhausts emission regulation without affecting the fuel economy of diesel engines [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the NO to NO 2 oxidation capacity does not match linearly to the soot combustion rate, because there are some other factors that influence this reaction, such as lattice oxygen mobility and production and transfer of "active oxygen", as reported in the literature for ceria-based catalysts [22,35]. In a recent preliminary study [36], the rate of soot combustion under isothermal conditions at 400°C shown by a copper-doped ceria-zirconia catalyst was very high, and only a little bit lower than that of a commercial Pt-catalyst in terms of mass of catalyst, but higher if the activity was expressed in terms of price of catalyst.…”
Section: Introductionmentioning
confidence: 99%